Description a new species of the genus Orphnebius Motschulsky, 1858 (Coleoptera: Staphylinidae: Aleocharinae) from Xizang, China - Jiang, Ri-Xin; Li, Bo-Yan; Wang, Shuo (Zootaxa, 2020)
A new species of the genus Orphnebius Motschulsky: Orphnebius lilizheni sp. nov. is described from Xizang, China. All specimens examined in this study were collected from the nest of an ant species Myrmica sp. (Hymenoptera, Formicidae). The adults and larvae of the new species are described, figured and compared with its congeners.